HEALTHY WAY OF LIFE: HEALTH BUILDING, HEALTH SAVING - Nelly Borisovna Pyastolova (Физическая культура. Спорт. Туризм. Двигательная рекреация, 2020)
The author considers various aspects of a healthy lifestyle, the need to maintain it in modern megacities, and its impact on the lifestyle of children, adolescents, and middle-aged people. It also addresses important compliance issues, problems of sleep deprivation and obesity in adolescents, and the need to develop a proper and balanced diet for school and preschool children. The article considers the likely consequences for those who do not follow a healthy lifestyle and have bad habits.